The associations of maternal and children’s gut microbiota with the development of atopic dermatitis for children aged 2 years - Fan, Xiaoxiao; Zang, Tianzi; Dai, Jiamiao; Wu, Ni; Hope, Chloe; Bai, Jinbing; Liu, Yanqun (Frontiers in Immunology, 2022)
Background It is critical to investigate the underlying pathophysiological mechanisms in the development of atopic dermatitis. The microbiota hypothesis suggested that the development of allergic diseases may be attributed to the gut microbiota of mother-offspring pairs. The purpose of this study was to investigate the relationship among maternal-offspring gut microbiota and the subsequent development of atopic dermatitis in infants and toddlers at 2 years old. Methods A total of 36 maternal-offspring pairs were enrolled and followed up to 2 years postpartum in central China. Demographic information and stool samples were collected perinatally from pregnant mothers and again postpartum from their respective offspring at the following time intervals: time of birth, 6 months, 1 year and 2 years. Stool samples were sequenced with the 16S Illumina MiSeq platform. Logistic regression analysis was used to explore the differences in gut microbiota between the atopic dermatitis group and control group. Results Our results showed that mothers of infants and toddlers with atopic dermatitis had higher abundance of Candidatus_Stoquefichus and Pseudomonas in pregnancy and that infants and toddlers with atopic dermatitis had higher abundance of Eubacterium_xylanophilum_group at birth, Ruminococcus_gauvreauii_group at 1 year and UCG-002 at 2 years, and lower abundance of Gemella and Veillonella at 2 years. Additionally, the results demonstrated a lower abundance of Prevotella in mothers of infants and toddlers with atopic dermatitis compared to mothers of the control group, although no statistical difference was found in the subsequent analysis. Conclusion The results of this study support that gut microbiota status among mother-offspring pairs appears to be associated with the pathophysiological development of pediatric atopic dermatitis.